The New Standard Based Curriculum in Ghana; Prospects, Challenges and the Way Forward. - Mochiah, James Nweah-Ackah; Adibi, Maria-Goretti Dunyo (Journal of Education and Practice, 2023)
Purpose: The study aimed at assessing the standard based curriculum recently introduced; the training given to teachers and the implementation challenges teachers are confronted with. Methodology: Descriptive design was employed for the study. Quantitative data was collected from 200 Basic School Teachers in the Western Region of Ghana using a questionnaire. Data on the two research questions were analyzed using mean and standard deviation. Also, One way ANOVA was used to test the two hypotheses formulated for the study. Findings: The findings of the study showed that teachers were adequately trained on the new standard based curriculum before its implementation. Unfortunately, the study revealed that teachers and students lack the recommended teaching and learning materials. Interestingly, the results showed that there is a significant difference in the implementation of the standard based curriculum among teachers with regards to their level of teaching. On the other hand, the test on teachers' academic qualification showed no significant difference. Unique contribution to theory, policy and practice: It was recommended that government should provide adequate teaching and learning materials for teachers and students to enhance the successful implementation of the new standard base curriculum. Head-teachers are encouraged to intensify supervision of teachers and provide feedback for smooth implementation of the new standard base curriculum. Finally, National Council for Curriculum and Assessment should constantly evaluate the implementation of the new curriculum to able be to address area areas that will more attention for successful implementation.